Travel Agents as Market Mavens: An Empirical Study on Travel Agencies in Izmir - Dogru, Humeira; Ertaş, Mehmet; Ertaş, Mehmet; Selin Yılmaz, Burcu; Selin Yılmaz, Burcu (Turizam, 2018)
Despite the developments in computer-mediated communication after the advent of the Internet, traditional word-of-mouth (WOM) marketing is still inﬂuential on consumers’ buying decision processes. As one of the WOM inﬂuencer groups, market mavens are information providers who aﬀect buying decision of other consumers with their product knowledge and marketplace expertise. The purpose of the study is to examine whether front-line employees working at travel agencies are market mavens or not. A survey of 120 travel agency employees was conducted using a structured questionnaire including open-ended questions as well. Descriptive statistics, parallel test, minimum average partial test, exploratory factor analysis, independent samples t-test, and correlation analysis were performed using SPSS 24.0 software. The conclusion of the study revealed that the front line employees in travel agencies had a tendency to give recommendations and share information as market mavens.